Evaluation of contamination of cow milk with various conditionally pathogenic microflora for mastitis: genera Staphylococcus - Borovic, Irina; Borovik, Irina; Borovik, I.; Borovik, I. V.; Borovuk, I. V.; Borovik, Iryna; Borovyk, I. V.; Borovuk, Iryna V.; Borovyc, I. V.; Боровик, Ірина Володимирівна; Davydenko, Pavel; Davydenko, Pavlo; et al. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, 2023)
The food safety issue of livestock products concerning insemination by opportunistic and accompanying microflora has attracted increasing attention from specialists. The ever-increasing trade and export of dairy and meat products from Ukraine to the EU countries requires constant monitoring of inoculation with mesophilic-aerobic and facultatively anaerobic microorganisms and psychrophilic microorganisms, in particular the genera Listeria and Yersinia, which survive and multiply at low temperatures and in salted and fermented products and pose a threat to human health. Milk and lactic acid products make up a significant part of the diet of a modern person. Therefore, constant control of raw materials from dairy enterprises for the production of milk and directly at enterprises for its processing is a guarantee of food safety. At the stage of milk production, due to violations of technological cycles of production (mastitis and contamination with antibiotics) and the spread of several diseases in Ukraine (paratuberculosis, tuberculosis, leptospirosis, brucellosis), milk from a herd of dairy cows poses a significant threat to human health due to the danger of mastitis milk and milk containing the causative agents of tuberculosis, brucellosis, leptospirosis, and recently there are more and more reports about the association of bovine paratuberculosis and human short bowel syndrome (Crohn's disease) mainly among the young population of Europe, which may be due to extreme variability and adaptive capacity mycobacteria. Питання безпеки харчових продуктів тваринництва щодо запліднення умовно-патогенною та супутньою мікрофлорою привертає все більшу увагу фахівців. Постійно зростаюча торгівля та експорт молочної та м'ясної продукції з України до країн ЄС вимагає постійного контролю за інокуляцією мезофільно-аеробними та факультативно-анаеробними мікроорганізмами, а також психрофільними мікроорганізмами, зокрема родами Listeria та Yersinia, які виживають та розмножуються за низьких температур, а також у солоних та ферментованих продуктах і становлять загрозу для здоров'я людини. Молоко та молочнокислі продукти складають значну частину раціону сучасної людини. Тому постійний контроль сировини з молочних підприємств для виробництва молока та безпосередньо на підприємствах з його переробки є гарантією безпеки харчових продуктів. На етапі виробництва молока, через порушення технологічних циклів виробництва (мастит та забруднення антибіотиками) та поширення в Україні низки захворювань (паратуберкульоз, туберкульоз, лептоспіроз, бруцельоз), молоко від стада молочних корів становить значну загрозу для здоров'я людини через небезпеку маститного молока та молока, що містить збудників туберкульозу, бруцельозу, лептоспірозу, а останнім часом з'являється все більше повідомлень про асоціацію паратуберкульозу великої рогатої худоби та синдрому короткої кишки людини (хвороба Крона) переважно серед молодого населення Європи, що може бути пов'язано з надзвичайною мінливістю та адаптивними можливостями мікобактерій.
Оцінка забруднення коров'ячого молока різною умовно-патогенною мікрофлорою для маститу: роди Staphylococcus
Боровик Ірина Володимирівна https://orcid.org/0000-0001-5958-8396 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835 Кулішенко Олег Миколайович https://orcid.org/0000-0001-6801-2380 Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494
Keywords: mesophilic aerobic and faculta-tive anaerobic microorganisms; мезофільні аеробні та факультативно-анаеробні мікроорганізми; milk and dairy products; молоко та молочні продукти; mastitis; мастит; contamination; забруднення; microbiological diagnostics; мікробіологічна діагностика; human health; здоров'я людини